Yield And Quality Of Fodder Oat (Avena Sativa L.) As Influenced By Sowing Dates, Fertility Levels And Cutting Management (Applied Biological Research, 2012)
A field experiment was conducted during 2009-10 and 2010-11 at  Research Farm, Division of Agronomy, SKUAST-K, Shalimar (J&K)  to assess the influence of sowing dates, fertility levels and cutting  management on yield and quality of forage oat. Early sowing gave higher green and dry fodder yields while high crude protein, low  crude fibre and high ash contents were observed in oats sown on  October 10. Green fodder and dry fodder yields and crude protein  content increased with increase in fertility level up to 150 kg N + 70 kg  P2O5 + 40 kg K2Oha-1. Double cut crop gave higher forage yield and  better quality traits as compared to single cut crop.
Keywords: Cutting management; oats; quality; sowing dates; yield